The role of the Azerbaijani intelligentsia in the progress of Azerbaijani women in the 19th century - Karaeva, Saadat (Вісник гуманітарних наук, 2026)
The main goal of the article was to shed light on the struggle for the freedom and rights of our women, who were deprived of rights in public life, science and education, and to evaluate this struggle, that is, the importance of educating our women, as an integral part of the general socio-political struggle of society. It is stated that if a woman wants to express herself, she must be educated. And it is for this reason that our enlightened, patriotic intellectuals, who spoke about the importance of cultural progress and studying science, worked for the development of science and culture, and took care of the education of Azerbaijani girls, despite the difficulties of that time. Methods and methodologies used. The article uses analysis and comparison methods to investigate the struggles of our intellectual thinkers and women in order to make their voices heard and break the chains of their condemnation. What is new in the article. For the first time, the author studied the problem of a woman having free will, the ability to independently decide her own destiny, not depending on anyone, based on the works of thinkers. Conclusions. Summarizing the objectives set out in the analysis, notes and comments, the author came to the conclusion that man and woman are two main elements that play a decisive role in the development of society. Just as it is impossible for one to live without the other, the superiority of one over the other should also be impossible. If this balance is disturbed, the greatest damage will be done to the existing society, to the people lagging behind in progress. For this reason, it is necessary to join hands and fight for the progress of the people and the state, and this can be achieved not by the superiority of one, but by maintaining the balance of equality. And thus, in order to ensure the comprehensive development of humanity, women were called upon to science and enlightenment, the elimination of vulgar customs and traditions was put forward, and the slogan was raised that women should be educated and actively participate in public affairs.